Immobilization of Candida rugosa lipase on polymer support for monoacylglycerol production as halal emulsifier - Hazimah binti Akbar Tajudin (International Institute of Halal Research and Training, International Islamic University Malaysia, 2018)
Halal emulsifier has a very high demand in the Halal industry market. The production of emulsifier using enzyme-based strategies provides an alternative solution for conventional emulsifier production. Due to the instability of biocatalyst, immobilization technology has been found to be a powerful tool to improve the performance of enzymes. The aim for this research is to optimize the immobilization conditions for Candida rugosa lipase attachment on poly (glycidyl methacrylate)-grafted-polyethylene/polypropylene microfibrous sheet (PGMA-g-PE/PP) through covalent bonding. A pretreatment was carried out on the polymer prior to immobilization and the amine group density on the chemically modified PGMA-g-PE/PP microfibrous sheet was found to be 3.33 mmol/g. The chemically modified microfibrous sheet was characterized by Fourier-transform infrared spectroscopy (FTIR-ATR) and field emission scanning electron microscope (FESEM). Response surface methodology (RSM) was applied to model and optimize the immobilization settings represented by three factors including immobilization time (2-6 h), pH (pH 7-9) and enzyme/support ratio (5.0-9.0 mg/cm2). A well-correlated significant model (p-value = 0.0003) was determined for the residual activity of the immobilized lipase (R2 = 0.9136). The enzymatic activity on p-nitrophenyl palmitate (pNPP) substrate achieved optimum under the conditions of 4.24 hrs, pH 8 and 8.51 mg/cm2 ratio of enzyme/support. The optimal reaction temperature and pH value in enzymatic reaction for both free and immobilized lipase were found to be 45 oC at pH 7 and 55 oC at pH 6, respectively. The pH endurance, storage and thermal stability of the immobilized lipase were remarkably enhanced. The immobilized lipase can be readily recovered and more than 50% of its activity was retained following 10 cycles. The kinetic parameters study showed that both Vmax and KM values were decreased from 0.16 mM/min and 4.69 mM to 0.15 mM/min and 2.86 mM, respectively after immobilization. Lastly, the immobilized lipase was evaluated for monoacylglycerol emulsifier production from Kenaf seed oil. Result showed that monoacylglycerol was detected by GC-TOF/MS. The results of this study suggested that the PGMA-g-PE/PP microfibrous sheet is a promising polymer support for enzyme immobilization with potential for Halal emulsifier production.